Carbon-free Car Structure and Trajectory Simulation Design for Clocking the "Long March" Route - Zhou Yanbo; Luo Qiang; Zhang Yiwei; Wang Jingyu; Feng Qin; Wang Yingsheng (Jixie chuandong)
According to the requirements of the 2022 China College Students Engineering Practice and Innovation Ability Competition, a self-propelled potential energy drive vehicle that can punch in designated trajectory points (simulating the Long March route) is designed and produced. The SolidWorks' Bezier curve is used to draw the fitted curve through a specific trajectory point. The fitting curve is further optimized and simulated by Matlab to obtain the cam profile that meets the design requirements. Combined the with laser dot fine-tuning mechanism, the SolidWorks reverse modeling method is used innovatively, the arc cam steering mechanism is designed, to improve the accuracy and repeatability of the car running trajectory. Finally, SoildWorks is used to establish a three-dimensional model of the carbon-free car and analyze its structure. The running results of the car show that the car walking trajectory has good repeatability and can punch all the specified trajectory points.